1991
DOI: 10.1029/90gl02036
|View full text |Cite
|
Sign up to set email alerts
|

Observations of correlated broadband electrostatic noise and electron cyclotron emissions in the plasma sheet

Abstract: Electric field wave observations in the central plasma sheet show the correlated occurrence of broadband electrostatic noise and electrostatic electron cyclotron harmonic emissions. A model is proposed in which the broadband emissions are electron acoustic waves generated by an observed low energy electron beam, and the cyclotron emissions are generated by the hot electron loss cone instability. The high degree of correlation between the two emissions is provided in the model by the presence of the cold electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
6
0
1
Order By: Relevance
“…The potential as a function of height above the lunar surface from the PIC model for three different cases of plasma sheet ion temperature, T i = 500, 1000, 2000 eV, for constant electron temperature, T e = 500 eV, and density, n ps = 10 5 m À3 . acoustic instability from the streaming photoelectrons and the instability of the loss cone anisotropy, similar to that outlined by Roeder et al [1991], especially given the high degree of correlation between the BEN and the presence of the photoelectron beam. We suggest that the presence of both BEN and electron cyclotron harmonic emissions near airless bodies can be used as a diagnostic in searching for surfacegenerated electron beams and possible non-monotonic potentials at other airless bodies [Gurnett et al, 1981;Kurth et al, 1987Kurth et al, , 2001Santolík et al, 2011].…”
Section: Comparison To Artemis Datasupporting
confidence: 58%
See 1 more Smart Citation
“…The potential as a function of height above the lunar surface from the PIC model for three different cases of plasma sheet ion temperature, T i = 500, 1000, 2000 eV, for constant electron temperature, T e = 500 eV, and density, n ps = 10 5 m À3 . acoustic instability from the streaming photoelectrons and the instability of the loss cone anisotropy, similar to that outlined by Roeder et al [1991], especially given the high degree of correlation between the BEN and the presence of the photoelectron beam. We suggest that the presence of both BEN and electron cyclotron harmonic emissions near airless bodies can be used as a diagnostic in searching for surfacegenerated electron beams and possible non-monotonic potentials at other airless bodies [Gurnett et al, 1981;Kurth et al, 1987Kurth et al, , 2001Santolík et al, 2011].…”
Section: Comparison To Artemis Datasupporting
confidence: 58%
“…The BEN is present at times when the beam is at relatively high energies, yet ceases when the beam has either disappeared (11:59-12:01) or when the beam is at a very low energy level (12:13-12:25). One possible mechanism for the generation of both the BEN and the previously mentioned electron cyclotron harmonic emissions may be the coupling of the electron acoustic instability from the streaming photoelectrons and the instability of the loss cone anisotropy, similar to that outlined by Roeder et al [1991], especially given the high degree of correlation between the BEN and the presence of the photoelectron beam. We suggest that the presence of both BEN and electron cyclotron harmonic emissions near airless bodies can be used as a diagnostic in searching for surfacegenerated electron beams and possible non-monotonic potentials at other airless bodies [Gurnett et al, 1981;Kurth et al, 1987Kurth et al, , 2001Santolík et al, 2011].…”
Section: Poppe Et Al: Artemis Lunar Dayside Observations L01102 L01102mentioning
confidence: 99%
“…Intense broadband electrostatic noise, extending from 100 Hz to several kHz, may be present outside the plasmapause during enhanced magnetic activity, especially on the night‐side [e.g., Roeder et al , 1991]. These emissions, which could contaminate the observations of the magnetosonic waves, were removed from the database using the following criteria.…”
Section: Crres Databasementioning
confidence: 99%
“…Due to the boundedness of sweep frequency receiver on board the CRRES spacecraft, Meredith et al () identified the band of waves between 0.5 f LHR < f < f LHR within 3° of the magnetic equator as MS waves at a reasonable coverage in 2 < L <7 . Since their criteria may include intense broadband electrostatic noises from 100 Hz to several kilohertz (Roeder et al, ), Meredith et al () eliminated the emissions, whose power‐spectral density (PSD) of electric field at 1.5 f LHR are both greater than 2.0 × 10 ‐4 mV 2 /Hz and within a factor of 5 for those at 0.75 f LHR . Němec et al () also gave a method to identify the EN emissions (here they call MS waves as equatorial noise, EN) for the observations of Cluster from 2001 to 2010, that is, fulfilling the conditions of planarity >0.8, ellipticity <0.2, and WNA >85°, with the spectrum frequency between 0 and 200 Hz.…”
Section: Introductionmentioning
confidence: 99%